Handbook of local anesthesia - Malamed, Stanley F. 1944- (Elsevier/Mosby, 2013)
A guide to safe anesthesia practices in dentistry. It the advances in science, instrumentation, and pain control techniques. It provides coverage of key anesthesia topics, including specific hazards and errors in technique that may result in complications.